Andrés Rivera recita su kaddish - Saúl Sosnowski (Cuadernos LIRICO)
Written a few years before his death, Kadish offers a glimpse of what also runs through the work of other Jewish Latin American authors, whether or not they are as intensely involved as Andrés Rivera in political militancy. Almost like in a fragmented apocryphal biography, we find here a sort of dialectic cut between the various components of someone who is aware of and demands his legitimate nationality, and whose Jewish identity is the mark of an imposed difference.